2020
DOI: 10.1108/ec-08-2019-0365
|View full text |Cite
|
Sign up to set email alerts
|

New cubic B-spline approximation technique for numerical solutions of coupled viscous Burgers equations

Abstract: Purpose The purpose of this paper is to present a new cubic B-spline (CBS) approximation technique for the numerical treatment of coupled viscous Burgers’ equations arising in the study of fluid dynamics, continuous stochastic processes, acoustic transmissions and aerofoil flow theory. Design/methodology/approach The system of partial differential equations is discretized in time direction using the finite difference formulation, and the new CBS approximations have been used to interpolate the solution curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…The author has concluded that a suitable optimal of the initial condition leads towards the vital exact solution after some iterative phases. Nazir et al 25 presented a new cubic B‐spline (CBS) approximation technique for the numerical treatment of coupled viscous Burgers equations arising in the study of fluid dynamics, continuous stochastic processes, acoustic transmissions and aerofoil flow theory. The authors have discretized the system of partial differential equations in time direction using the finite difference formulation, and they have used the new CBS approximations to interpolate the solution curves in the spatial direction.…”
Section: Introductionmentioning
confidence: 99%
“…The author has concluded that a suitable optimal of the initial condition leads towards the vital exact solution after some iterative phases. Nazir et al 25 presented a new cubic B‐spline (CBS) approximation technique for the numerical treatment of coupled viscous Burgers equations arising in the study of fluid dynamics, continuous stochastic processes, acoustic transmissions and aerofoil flow theory. The authors have discretized the system of partial differential equations in time direction using the finite difference formulation, and they have used the new CBS approximations to interpolate the solution curves in the spatial direction.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical solutions have been extracted from this conformable Sumudu transform, and conformable fractional derivatives were solved to construct the new exact traveling wave solutions of the three special form of time fractional WKB equations [11][12][13], such as the time fractional approximate long-wave equations, the time fractional variant Bossiness equations, and the time fractional Wuzhang system of equations using the generalized exp ðϕðξÞÞ expansion [14] method with a conformable derivative sense. They have presented a new cubic B-spline (CBS) approximation technique for the numerical treatment of coupled viscous Burgers' equations arising in the study of fluid dynamics, continuous stochastic processes, acoustic transmissions, and aerofoil flow theory [15]. A finite difference scheme which depends on a new approximation based on an extended cubic B-spline for the second-order derivative is used to calculate the numerical outcomes of time fractional Burgers Equation ( 22).…”
Section: Introductionmentioning
confidence: 99%
“…Spline interpolation is a form of interpolation where the interpolant is a special type of piecewise polynomial called a spline. Applications of spline function in fractional partial differential equations can be found in [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%